Jelenšek above Godovič (Slovenia).: Hillfort and cemetery from the Early Iron Age - Bratina, Patricija; Laharnar, Boštjan; Svoljšak, Drago (Arheološki vestnik, 2022)
The saddle north of the hillfort on Jelenšek, an elevation above Godovič near Idrija, is the site where two seekers of a ‘pagan treasure from Jelenšek’ stumbled upon Iron Age burials with rich goods. This discovery was followed by rescue archaeological excavations in 1993 that unearthed 37 flat cremation burials. The goods are quite uniform and date to the Late Hallstatt phases of Sv. Lucija IIb2 and IIc. The interred individuals were warriors, one a craftsman (foundryman), women and possibly also children. The article briefly presents the burial rite, grave goods and dating of the site based on fibulae. This is followed by a discussion on the significance of the site in the Early Iron Age, when Jelenšek lay at the border between two Hallstatt groups of western Slovenia, namely the Posočje (Sveta Lucija) and Notranjska-Kras groups.